2014
DOI: 10.18475/cjos.v48i1.a5
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variability in Drought as a Function of the Atlantic Multidecadal Oscillation

Abstract: Thus, the findings of this research can assist in informing drought preparedness strategies to mitigate significant losses due to drought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
(42 reference statements)
0
4
0
Order By: Relevance
“…In much of the tropics, the El Niño phase of ENSO is associated with drier, sunnier, and hotter conditions, whereas the La Niña phase is associated with wetter, cloudier, and cooler conditions (Holmgren, Scheffer, Ezcurra, Gutiérrez, & Mohren, 2001;Marengo, Tomasella, Alves, Soares, & Rodriguez, 2011). The AMO also influences climate variation at our site and other areas in the region (Elder, Balling, Cerveny, & Krahenbuhl, 2014). Tropical tree recruitment, growth, and mortality all vary among years in relation to such local climate variation, and thus, stand-level productivity and mortality fluxes vary as well.…”
Section: Temporal Climate Variation In the Tropics And Its Impactsmentioning
confidence: 83%
“…In much of the tropics, the El Niño phase of ENSO is associated with drier, sunnier, and hotter conditions, whereas the La Niña phase is associated with wetter, cloudier, and cooler conditions (Holmgren, Scheffer, Ezcurra, Gutiérrez, & Mohren, 2001;Marengo, Tomasella, Alves, Soares, & Rodriguez, 2011). The AMO also influences climate variation at our site and other areas in the region (Elder, Balling, Cerveny, & Krahenbuhl, 2014). Tropical tree recruitment, growth, and mortality all vary among years in relation to such local climate variation, and thus, stand-level productivity and mortality fluxes vary as well.…”
Section: Temporal Climate Variation In the Tropics And Its Impactsmentioning
confidence: 83%
“…To the authors' knowledge, such correlations had not been previously described for our study region, but Montero‐Martínez et al (2022) reported an increase in precipitation and temperature during AMO positive phase in central Mexico. Also, Elder et al (2014) and Park et al (2017) described an influence of AMO and PDO in drought events in Mexico, which stress the importance of keeping track of these ocean–atmosphere oscillations in future assessments of local climate trends.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent El Niño conditions extended from September 2018 through May 2019 causing widespread drought. Given that Elder et al (2014) found a positive correlation between drought conditions between the AMO and the Standardized Precipitation Evapotranspiration Index (SPEI; negative values of SPEI indicate drought). it appears that combined AMO and El Niño-like conditions contributed to the severe drought that Barbuda faced in 2018/2019.…”
Section: Future Climate Change In Barbudamentioning
confidence: 99%